Analysis of the influence of binder properties on the mechanical response of bituminous mixtures. Issue Volume 18:Issued 1(2017) (2nd January 2017) - Moreno-Navarro, F.; Sol-Sánchez, M.; Jiménez del Barco, A.; Rubio-Gámez, M.C.
Abstract: Asphalt mixtures are composed by a mass of aggregates (more than 90% of their total weight), which are bonded by a bituminous binder. Despite the fact that the binder is not the main component of these materials (around 5% of their total weight), it exerts a high influence on their mechanical response. In this sense, the service life of asphalt pavements will directly depend on the type of binder used, and thus an adequate choice is crucial to construct more durable roads. Because of this fact, it is necessary to know the characteristics of the bitumen in order to reduce the impact of different distresses that appear on roads. For this purpose, this paper studies the influence of the binder properties in the appearance of the main distresses that affect asphalt pavements around the world (stripping, fatigue cracking and plastic deformations). Five bitumens with different properties have been analysed during this research using diverse binder (UCL, multiple stress creep and recovery test and dynamic shear rheometer time sweep) and mixture (water sensitivity, wheel tracking and UGR-FACT) tests. The results obtained show that the properties of the binder influence the long-term performance of bituminous mixtures. In this sense, it can be said that flexible binders which are able to recover plastic deformations could extend the service life of the pavements.